Sistem Informasi Reservasi Tamu pada SEI Hotel Banda Aceh (Yayasan Kawanad, 2023)
The Guest Reservation Information System is an important aspect of data management at SEI Hotel. The aim is to simplify and direct the acquisition of information related to guest reservation reports. In this research, the author discusses the design of a Guest Reservation Information System at SEI Hotel using the CodeIgniter framework. Programming is carried out using HTML, PHP, CSS, JSON, AJAX, and MySQL as database support. This research aims to design a Guest Reservation Information System at SEI Hotel using the CodeIgniter framework and using the programming languages HTML, PHP, CSS, JSON, AJAX, and MySQL as database support. Data collection was carried out through two methods, namely library studies which included library book literature and related scientific works, as well as field studies by conducting interviews and direct observation of research objects. The guest reservation process at SEI Hotel is carried out by an administrative staff in the financial sector, who is tasked with recording and inputting guest reservation report data. The research results show that the Guest Reservation Information System at SEI Hotel has followed procedures using the CodeIgniter framework and the programming languages HTML, PHP, CSS, JSON, AJAX, and MySQL as database support